Altman Financial Distress Model Comparison Prediction on Listing and Delisting Companies - Aprisa Kusumawati; Suripto Suripto; K. Bagus Wardianto (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to compare the effectiveness of the financial ratios Working Capital to Total Assets (WCTA), Retained Earnings to Total Assets (RETA), Earnings Before Interest and Tax to Total Assets (EBITTA), and Book Value of Equity in the Altman model when predicting financial distress in companies listed and delisted on the IDX during the period 2018-2023. Financial distress is an event in which a company experiences financial difficulties that can lead to bankruptcy. This study uses secondary data generated through the company's annual financial reports listed on the IDX. The analysis method used is multiple discriminant analysis (MDA) to identify the probability of each financial ratio in the occurrence of financial distress. The results of this study are expected to provide insight for financial managers and investors when anticipating and managing financial risks, as well as contributing to academic literature related to financial distress prediction. In addition, this study also shares an overview of the effectiveness of the Altman model in the context of the Indonesian capital market during the period analyzed.